2008
DOI: 10.1128/jb.00996-08
|View full text |Cite
|
Sign up to set email alerts
|

PilF Is an Outer Membrane Lipoprotein Required for Multimerization and Localization of thePseudomonas aeruginosaType IV Pilus Secretin

Abstract: Type IV pili (T4P) are retractile appendages that contribute to the virulence of bacterial pathogens. PilF is a Pseudomonas aeruginosa lipoprotein that is essential for T4P biogenesis. Phenotypic characterization of a pilF mutant confirmed that T4P-mediated functions are abrogated: T4P were no longer present on the cell surface, twitching motility was abolished, and the mutant was resistant to infection by T4P retraction-dependent bacteriophage. The results of cellular fractionation studies indicated that PilF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 72 publications
4
111
0
1
Order By: Relevance
“…These include the major pilin subunit PilA, as well as a conserved set of minor pilin-like proteins (21); the N-methyltransferase/peptidase PilD, essential for processing prepilins into their mature form (53); an inner membrane assembly subcomplex composed of PilM/N/O/P (4,47); an outer membrane PilQ secretin pore oligomerized with the assistance of the lipoprotein PilF (7,29); and the motor ATPases PilB and PilT/U (12,54,57), involved in pilus extension and retraction, respectively. The gene encoding FimV was originally identified in a transposon mutagenesis screen for P. aeruginosa mutants defective in twitching motility, but its role was not defined (50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These include the major pilin subunit PilA, as well as a conserved set of minor pilin-like proteins (21); the N-methyltransferase/peptidase PilD, essential for processing prepilins into their mature form (53); an inner membrane assembly subcomplex composed of PilM/N/O/P (4,47); an outer membrane PilQ secretin pore oligomerized with the assistance of the lipoprotein PilF (7,29); and the motor ATPases PilB and PilT/U (12,54,57), involved in pilus extension and retraction, respectively. The gene encoding FimV was originally identified in a transposon mutagenesis screen for P. aeruginosa mutants defective in twitching motility, but its role was not defined (50).…”
mentioning
confidence: 99%
“…Rabbit polyclonal antisera were generated by Cedarlane (Burlington, Ontario, Canada). The antisera raised against PilM/N/O/P/Q/F and PilA were described previously (4,24,29).The expression vectors pET28a-fimV66-1170, pET151-fimV67-387, and pET151-fimV67-762 (Table 1) were transformed into E. coli BL21-Codon Plus-RIPL and grown in LB with ampicillin at 100 mg/liter at 37°C to an OD 600 of 0.5 to 0.6, when protein expression was induced using 1.0 mM IPTG. Cells were harvested after 3 to 4 h. Cells were resuspended in lysis buffer containing 500 mM KCl, 0.1% LDAO (lauryldimethylamine oxide), 20 mM Tris, pH 8.0, 10 ng/ml of DNase and RNase, and a cocktail of protease inhibitors prior to lysis via sonication and centrifuged at 50,000 ϫ g. The soluble fraction was applied to a preequilibrated 5-ml His-trap nickel column (Amersham).…”
mentioning
confidence: 99%
“…Constructs containing the desired Cys substitutions, pEX18Gm::pilMNOP for PilNO Cys mutants and pEX18Gm::pilNOP for PilO Cys mutants, were introduced into E. coli SM10 cells for biparental mating with PAK pilN::FRT and PAK pilO::FRT, respectively (12). The E. coli SM10 donor was counter-selected by plating on Pseu- Major cell compartments are labeled as follows: inner membrane (IM), peptidoglycan (PG), and outer membrane (OM).…”
Section: Methodsmentioning
confidence: 99%
“…6, B and C), suggesting that the PilNO interface no longer adopts an orientation permissive for disulfide bond formation. New crystal structures of a P. aeruginosa PilM homodimer and of monomeric PilM fused to part of its binding partner, PilN (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), revealed that in the absence of PilN, the seven N-terminal residues of PilM (PilM (1-7)) bind in the PilN binding cleft of a second PilM monomer (41). Thus, PilM dimerizes in the absence of PilN.…”
Section: Piln and Pilo Homodimers May Represent A Functional Rather Tmentioning
confidence: 99%
“…The pilQ gene encodes a secretin through which the major pilin is secreted across the outer membrane. Assembly of this secretin requires its cognate pilotin, PilF, an outer membrane lipoprotein involved in the correct localization and multimerization of PilQ [32]. Furthermore, in contrast to PilB, which is involved in the assembly and extension of type IV pilin, PilT and PilU promote disassembly and retraction of the pilin.…”
Section: Both Vib15rifmentioning
confidence: 99%